Anxiety and satisfaction toward online learning on academic engagement during Covid-19 outbreak among Malaysian undergraduates - Ling, Leong Su; Ashari, Asmidawati; Kahar, Rojanah (Human Resource Management Academic Research Society, 2022)
This study aims to determine the relationship between anxiety and satisfaction towards online learning with student academic engagement during Covid-19 pandemic among local university students. A total of 203 students from four faculties in University Putra Malaysia, Serdang were involved in the study. Data were obtained using an online questionnaire form. Findings showed that anxiety and satisfaction toward online learning were significantly correlate with the academic engagement among students. Multiple regression analysis showed that two factors were found to have significantly predicted students' academic engagement namely state anxiety (? = 0.167, p <0.05), and response satisfaction toward online learning (? = 0.486 p <0.001). The model explained 34% of the variance in academic engagement among UPM students. Results of the present study revealed that access in satisfaction toward online learning is important in influencing the academic engagement of local UPM students. By understanding the aspects that have a high impact on local UPM students, it helps government agencies and higher education institutions to reduce mental health problems and online learning problems.